How National Zakat Board of Republic Indonesia (BAZNAS) Could Raise Zakat Funds: Riau Province Evidence - Ika Febriana; Idqan Fahmi; Moch. Hadi Santoso (Department of Islamic Economics, IPB University, 2022)
As a province in Indonesia with a majority Muslim population of 87.58%, Riau has a very large potential, reaching Rp 8.4 trillion but the highest realization that was collected by National Zakat Board (BAZNAS) of Riau Province was only Rp 12.15 billion in 2019. This zakat management organization (ZMO) has made various efforts in order to increase the zakat funds. This study analyzed the performance of this institution according to muzakki and recommended strategies to increase the number of muzakki and zakat funds. Using the Structural Equation Modeling (SEM) method, according to muzakki, BAZNAS of Riau Province has good transparency, accountability, socialization, and service quality. However, muzakki prefer to pay zakat in mosques and directly to mustahik. Therefore, this study recommended to increase collaboration with mosque administrators, increase numbers of Zakat Collecting Unit (ZCU) as fund collectors and also distributors, update websites regularly, and increase socialization with materials on procedures for paying zakat and the benefits of paying zakat through ZMO.